Correlates of viral suppression among HIV-infected men who have sex with men and transgender women in Lima, Peru - Rich, Katherine M.; Valencia Huamaní, Javier; Kiani, Sara N.; Cabello, Robinson; Elish, Paul; Florez Arce, Jorge; Pizzicato, Lia N.; Soria, Jaime; Wickersham, Jeffrey A.; Sanchez, Jorge; Altice, Frederick L. (Taylor & Francis, 2018)
In Peru, HIV is concentrated among men who have sex with men (MSM) and transgender women (TGW). Between June 2015 and August 2016, 591 HIV-positive MSM and TGW were recruited at five clinical care sites in Lima, Peru. We found that 82.4% of the participants had achieved viral suppression (VS; VL < 200) and 73.6% had achieved maximal viral suppression (MVS; VL < 50). Multivariable modeling indicated that patients reporting transportation as a barrier to HIV care were less likely to achieve VS (aOR = 0.47; 95% CI = 0.30–0.75) and MVS (aOR = 0.56; 95% CI = 0.37–0.84). Alcohol use disorders were negatively associated with MVS (aOR = 0.62; 95% CI = 0.30–0.75) and age was positively associated with achieving MVS (aOR = 1.29; 95% CI = 1.04– 1.59). These findings underscore the need for more accessible HIV care with integrated behavioral health services in Lima, Peru.